Receptor revision in CD4 T cells is influenced by follicular helper T cell formation and germinal center interactions - Higdon, Lauren Elizabeth (My University, 2014)
T cells produce diverse antigen receptors, including some with self-reactive specificities, through a process of somatic gene rearrangement. During the course of T cell development in the thymus, central tolerance eliminates self-reactive T cells. Self-reactive T cells that escape from the thymus can be tolerized in the periphery by multiple mechanisms including anergy and deletion. Peripheral CD4 T cells expressing Vβ5 undergo tolerance to an endogenous superantigen encoded by mouse mammary tumor virus 8 (Mtv-8) by either deletion or T cell receptor (TCR) revision. Revision is a process by which surface expression of the Vβ5+ TCR is downregulated and recombination activating genes are expressed to drive rearrangement of the endogenous TCRβ locus, effecting cell rescue through the expression of a newly generated, non self reactive TCR. Previous research has conclusively demonstrated the extrathymic nature of revision, but the regulatory context in which this process takes place remains unclear. Revision is known to occur in the germinal center (GC), a site in which B cells and T cells interact to promote memory B cell formation and high-affinity antibody responses. GCs have a highly specific structure and require distinct cell interactions, which could contribute to a regulatory environment for revision. In this thesis, we present evidence that revising T cells phenotypically and functionally resemble follicular helper T cells, the T cells found in GCs, and that GCs are required for efficient revision. The GC is known to provide a confined space in which B cell antigen receptors undergo selection. Our data extend the role of this selective microenvironment into the arena of T cells, suggesting this fluid structure also provides a regulatory environment in which TCR revision can safely take place.
Thesis (Ph.D.)--University of Washington, 2014
Keywords: follicular helper T cells; germinal centers; Rag-mediated recombination; T cell tolerance; TCR revision; Immunology; molecular and cellular biology